Community policing - Rukus, Joseph (Crime & delinquency, 2018)
Little is known about the level or impact of community policing in suburban and rural communities. We surveyed more than 1,300 cities and counties and asked city managers about social cohesion, collective efficacy, and community policing variables. We find no effect of community policing on perception of safety and a positive effect on community participation only in the metro core. For suburbs and rural areas, community policing is only related to youth services. Collective efficacy is positively associated with safety perceptions across all communities but only related to community participation in suburbs and low crime communities. These results raise questions on how to better link collective efficacy and community policing in high crime communities, especially in suburbs and rural areas.